Ethical Problems, Ethical Interrogations and Ethical Responses - Eegunlusi, Tayo Raymond Ezekiel Eegunlusi (African Journal of Stability and Development (AJSD), 2024)
By showing how philosophers probe into and respond to ethical issues, this paper discusses the nature of ethical problems. It examines the contentions between traditional and non-traditional ethical perspectives by evaluating the ideas of certain philosophers that cast aspersion on traditional views of ethics. It equally responded to these thinkers’ opinions. Engaging conceptual and historical analyses, the paper delves into certain critical issues involved in ethics and ethical interrogations, relative to the issues raised by these thinkers. Thus, while not denying that these thinkers’ ideas have some merit, the paper holds that their arguments focused on subverting traditional ethics and ethical terms threatening normative ethics as well as human everyday moral (virtuous) existence. It avers that the collapse of normative ethical thinking and acts can engineer societal moral conflicts.